A STUDY OF MEDICINE MANAGEMENT IN PUBLIC HEALTH CENTER - Sari, Nur Mila; Napirah, Muhammad Ryman; Windy, Widy Try (Universitas Banten Jaya, 2025)
In Indonesia, drug expenditures that have been roughly fourty percent are seen as exorbitant. Drug availability is decreased, pharmaceuticals become scarce, a large number of drugs accumulate as a result of poor drug planning, and irrational drug use drives up drug costs. The aim to Find out about the Public Health Center's drug needs planning, distribution, storage, and recording and reporting is the goal. design of qualitative research using a case study methodology. In their working area, the Public Health Center and Integrated Service Center, this study was carried out in 2017. The Public Health Center's director served as the study's primary informant. The result is Public Health Center and the Health Office collaborate to plan for drug needs; nonetheless, some medications are required but not included in the e-catalog. The Public Health Center's drug storage is set up according to the FIFO and FEFO systems, but there are no dedicated cabinets for narcotics and psychiatric medications, and the air temperature does not yet meet regulations. Unavailable medications cause problems with patient medicine distribution, leading to ineffective and inefficient services. Due to a shortage of pharmaceutical health workers, drug recording and reporting are not completed on time. According to the study's findings, there are challenges with drug management at the Public Health Center, ranging from organizing drug requirements, storing, distributing, and recording and reposrting drugs.